Likuiditas, Kebijakan Dividen, Leverage, Non-Performing Loan dan Nilai Perusahaan Bank BUMN yang Go Public - Azhar Latief (Politeknik Ganesha Medan, 2022)
Economic development in Indonesia began with the development of the banking industry. As a company, the bank cannot override its primary objective. The main objective of a company is to increase the firm value. This study aims to determine how the effect of liquidity, dividend policy, leverage, and non-performing loans on the firm value of state-owned banks that go public in Indonesia. The population in this study is state-owned banks listed on the Indonesia Stock Exchange (IDX). The method used is a non-probability sampling method with a purposive sampling technique and obtained 4 state-owned banks were used as samples for a research period of 10 years (2011-2020). The data analysis technique used is Structural Equation Modeling Partial Least Square (SEM-PLS) with the help of SmartPLS (v. 3.2.9) software as a data analysis tool. The results of this study showed that liquidity and non-performing loans have a significant effect on firm value. Dividend policy and leverage have no significant impact on firm value. Further research can add other variables that affect the value of banking companies, such as profitability, Capital Adequacy Ratio (CAR), Debt to Equity Ratio, company size, and company growth. Also can conduct research in other sectors such as manufacturing, mining, and pharmaceuticals.